UNBURNED HYDROCARBON EMISSION MECHANISMS IN SMALL ENGINES - Salazar, Victor M. (My University, 2009)
The effect of the liquid fuel in the intake manifold, the ring pack crevices and the oil film on the unburned hydrocarbon (HC) emissions of a spark-ignited, carbureted, air-cooled V-twin engine was studied. Tests were performed for a range of engine load, two engine speeds, various air-fuel ratio and with a fixed ignition timing. To isolate liquid fuel effects due to the poor atomization and vaporization of the fuel when using a carburetor, a specially conditioned homogeneous, pre-vaporized mixture system (HMS) was developed. The results from carburetor and HMS are compared. To verify the existence of liquid fuel in the manifold, and to obtain an estimate of its mass, a carburetor-mounted liquid fuel injection (CMLFI) system was also implemented. Stop-injection tests performed with the CMFLI system show that 60-80 cycles worth of liquid fuel is held in the intake manifold depending on operating condition. The results of the comparison show that the liquid fuel in the intake manifold does not have a statistically significant influence on the averaged HC emissions. In addition, the cycle-resolved HC emissions for both systems follow the same trends and are comparable in magnitude. Heat release analysis showed little difference between fuel mixture delivery system. These results suggest that under steady state operation the HC emissions for this engine are not sensitive to the presence of liquid fuel in the intake manifold. The ring pack contribution to the engine-out HC emissions was estimated using a simplified ring pack gas flow model; the model was tested against the experimentally measured blowby. The tests were performed using the homogeneous fuel mixture system. The integrated mass of HC leaving the crevices from the end of combustion (the crank angle that the cumulative burn fraction reached 90%) to exhaust valve closing was taken to represent the potential contribution of the ring pack to the overall HC emissions; post-oxidation in the cylinder will consume some of this mass. Time-resolved exhaust HC concentration measurements were also performed, and the instantaneous HC mass flow rate was determined using the measured exhaust and cylinder pressure. At high load the model predicts that the ring pack returns approximately three times as much HC mass to the cylinder as is measured in the exhaust, indicating that the HC emissions are dominated by the ring pack contribution. At the lightest load condition tested, the ring pack model predicts less mass returning to the cylinder from the ring pack than is observed in the exhaust, clearly indicating that another HC mechanism is significantly contributing to the exhaust HC emissions. The integrated exhaust HC mass from the time-resolved HC measurement was found to correlate inversely with the IMEP on a cycle-by-cycle basis, which strongly suggest that incomplete combustion is materially contributing to the exhaust HC emissions. A statistical analysis showed that the correlation was significant. The intermediate load condition represents a combination of these two extremes. The ensemble-average ring pack model results indicate that the mass returned to the cylinder from the ring pack is slightly higher than the amount measured in the exhaust. But, a conditional sampling analysis indicates that there are sub-groups, i.e. late-burning cycles, for which this is not true. There is expected to be some in-cylinder post-oxidation of the ring pack HC mass at this condition, and the late burning cycles were not found to excessively contribute to the HC emissions, which both strongly suggests that there are other mechanisms besides the ring pack that are significantly contributing to the HC emissions at this condition. The most likely mechanism is incomplete combustion. The contribution of fuel adsorption in engine oil and its subsequent desorption following combustion to the engine-out hydrocarbon (HC) emissions was studied by comparing steady state and cycle-resolved HC emission measurements from operation with a standard full-blend gasoline, and with propane, which has a low solubility in oil. Experiments were performed at two speeds and three loads, and for different mean crankcase pressures. The crankcase pressure was found to impact the HC emissions, presumably through the ringpack mechanism, which was largely unaltered by the different fuels. The average and cycle-resolved HC emissions were found to be in good agreement, both qualitatively and quantitatively, for the two fuels. Further, the two fuels showed the same response to changes in the crankcase pressure. The experiments were supported by a numerical analysis. The simulation of the liquid-gas phase equilibrium of the fuel-oil system showed the solubility of propane in the oil was approximately an order of magnitude lower than for gasoline. Further the numerical analysis of the adsorption-desorption of the fuel in the oil along the cycle showed that the oil layer contribution is very small compared with the ring pack contribution. This suggests that the effect of fuel adsorption in the oil is not significant for small air-cooled utility-type engines.